Structure material physic-mechanical characteristics accuracy determination while changing the level of stresses in the structure - Kolokhov, Victor; Колохов, Віктор; Sopilniak, Artem; Сопільняк, Артем; Gasii, Grygorii; Гасій, Григорій; Kolokhov, Alexander; Колохов, Олександр (Science Publishing Corporation, 2018)
The reliability and durability of building structures is largely connected with the determination of the physic-mechanical characteristics (PMH) of a concrete structure, their measurement (determination) is the most critical procedure. The process of measuring physic-mechanical characteristics materials is characterized by various errors, which are divided into gross, systematic and random. The influence of systematic errors is taken into account by using various kinds of calibration (or gauging) dependencies which use non-destructive testing devices. The analysis of the presented results shows that the reliability of the belonging of concrete of different series to one general aggregate is rather low. This meant that the application of tariation dependencies, graduated for concrete in one series, will lead to significant errors in the determination of PMH for concrete of other series. Therefore, to clarify the physicomechanical characteristics of materials, it is necessary to use data on the level of stress-strain state of the structure. Надійність і довговічність будівельних конструкцій значною мірою пов'язана з визначенням фізико-механічних характеристик (ФМХ) бетонної конструкції, їх вимірювання (визначення) є найбільш відповідальною процедурою. Процес вимірювання фізико-механічних характеристик матеріалів характеризується різними похибками, які поділяються на грубі, систематичні та випадкові. Вплив систематичних похибок враховується за допомогою різного роду калібрувальних (або вимірювальних) залежностей із застосуванням приладів неруйнівного контролю. Аналіз наведених результатів показує, що достовірність приналежності бетонів різних серій до одного загального заповнювача досить низька. Це означало, що застосування таріаційних залежностей, градуйованих для бетонів однієї серії, призведе до суттєвих похибок у визначенні PMH для бетонів інших серій. Тому для уточнення фізико-механічних характеристик матеріалів необхідно використовувати дані про рівень напружено-деформованого стану конструкції.
Точність визначення фізико-механічних характеристик конструкційного матеріалу при зміні рівня напружень у конструкції
Keywords: building structures; будівельні конструкції; physical and mechanical characteristics of materials; фізико-механічні характеристики матеріалів; reliability and durability; надійність і довговічність; level of stress-strain state of the structure; , рівень напружено-деформованого стану конструкції